2020
DOI: 10.1111/ppc.12694
|View full text |Cite
|
Sign up to set email alerts
|

Association between depression or sleep problems and working time mismatch among Korean workers

Abstract: Purpose: This study aimed to investigate the relationship between South Korean workers' working time mismatches and their depression and sleep disorders.Design and Methods: This study used raw data from the fifth Korean Working Conditions Survey (KWCS), which sampled 50,205 workers. Findings:The risk of occurrence of sleep problems among workers was shown to be proportional to actual working time. The risk of occurrence of depression increased along with the degree of working time mismatch.Practice Implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Researcher's interests have shifted towards the effect of overemployment (working more than desired hours) and underemployment on individuals well-being, based on the fact that each worker's desired working hours is different [14]. Also in South Korea, the number of studies performed on working time mismatch and resultant health problems has increased recently, and studies have reported that working time mismatch is related to subjective well-being, stress, and depression [15,16] and that individuals with larger working time mismatch are at greater risk of depression [17,18]. A study based on the panel survey data from Australia and Germany suggested that in regard to workers' mental health, working time mismatch should be considered more than actual working hours [19].…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researcher's interests have shifted towards the effect of overemployment (working more than desired hours) and underemployment on individuals well-being, based on the fact that each worker's desired working hours is different [14]. Also in South Korea, the number of studies performed on working time mismatch and resultant health problems has increased recently, and studies have reported that working time mismatch is related to subjective well-being, stress, and depression [15,16] and that individuals with larger working time mismatch are at greater risk of depression [17,18]. A study based on the panel survey data from Australia and Germany suggested that in regard to workers' mental health, working time mismatch should be considered more than actual working hours [19].…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…However, there are few studies that have confirmed the association between working time mismatch and depression, while considering the actual working hours. Working hours per week and working time mismatch are known to affect depression, respectively [8,17,18]. Accordingly, this study was performed to determine relationships between working time mismatch and depression stratified by weekly working hours.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%